The Order of Organization of Supply Chain Management of Medical Industry Activity in The Republic of Tatarstan - N. N. Naumova; F. I. Kharisova (International Journal of Supply Chain Management, 2020)
Abstract—Supply chain management is a key mechanism to increase the efficiency of a medical industry activity. Purpose of this article is to examine the current state of supply chain management in healthcare institutions and offer instructions on supply chain management service organization in medical institutions. The author assesses current status of the supply chain management of activities of medical institutions by interviewing the owners, management, employees of individual healthcare institutions. The author identifies weaknesses in organization of the supply chain management in medical institutions and gives recommendations concerning the order of organization, principles, and fundamental rules as the basis for effective functioning of the supply chain management service in medical institutions. Organization of supply chain management becomes mandatory for many companies of the financial sector, including healthcare sector